2011
DOI: 10.1051/0004-6361/201116509
|View full text |Cite
|
Sign up to set email alerts
|

A minor merger origin for stellar inner discs and rings in spiral galaxies

Abstract: Context. Observations have shown that inner discs and rings (IDs and IRs) are not preferably found in barred galaxies, which indicates that their formation may differ from that described by the traditional bar-origin scenario in many cases. In contrast, the role of minor mergers in producing these inner components (ICs), while often invoked, is still poorly understood. Aims. We investigate the capability of minor mergers to trigger the formation of IDs and IRs in spiral galaxies through collisionless N-body si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 139 publications
(223 reference statements)
1
73
0
Order By: Relevance
“…In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000). The use of the Sérsic index (in addition to rotation) to identify pseudo-bulges is thus a dangerous practice.…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value. While pseudo-bulges are expected to have exponential-like surface brightness profiles (n 1 sph  ), being disky components that formed from their surrounding exponential disks (e.g., Bardeen 1975;Hohl 1975;Combes & Sanders 1981;Combes et al 1990;Pfenniger & Friedli 1991), it has been shown that mergers can create bulges with n 2 sph < (e.g., Eliche-Moral et al 2011;Scannapieco et al 2011;Querejeta et al 2015), just as low-luminosity elliptical galaxies (not built from the secular evolution of a disk) are also well known to have n 2 sph < and even n 1 sph < (e.g., Davies et al 1988;Young & Currie 1994;Jerjen et al 2000). The use of the Sérsic index (in addition to rotation) to identify pseudo-bulges is thus a dangerous practice.…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…In addition, residual star formation in early-type (E/S0) galaxies at z 0.7 can also be explained by minor merging (Kaviraj et al 2009. This problem has also been analysed by Eliche-Moral et al (2010a), who have modelled the evolution of luminosity function backwards in time for M 10 11 M galaxies, selected according to their colours (red/blue/total) and their morphologies. They find that the observed luminosity function evolution can be explained naturally by the observed gas-rich and dry major merger rates and that 50-60% of today's E/S0 in this mass range were formed by major mergers at 0.8 < z < 1, with a small number evolution since z = 0.8 (see also Cristóbal-Hornillos et al 2009;van der Wel et al 2009;Ilbert et al 2010;Eliche-Moral et al 2010b).…”
Section: Major Merger Rate: Close Pairs Vs Morphological Criteriamentioning
confidence: 99%
“…This problem has also been analysed by Eliche-Moral et al (2010a), who have modelled the evolution of luminosity function backwards in time for M 10 11 M galaxies, selected according to their colours (red/blue/total) and their morphologies. They find that the observed luminosity function evolution can be explained naturally by the observed gas-rich and dry major merger rates and that 50-60% of today's E/S0 in this mass range were formed by major mergers at 0.8 < z < 1, with a small number evolution since z = 0.8 (see also Cristóbal-Hornillos et al 2009;van der Wel et al 2009;Ilbert et al 2010;Eliche-Moral et al 2010b). The gas-rich major merger fractions assumed by ElicheMoral et al (2010a) are those from L09 for B-band selected galaxies (M B ≤ −20), which were obtained in a similar way than the morphological merger fractions used through present paper.…”
Section: Major Merger Rate: Close Pairs Vs Morphological Criteriamentioning
confidence: 99%
“…This fresh supply of gas can be effectively converted to stars causing nuclear starburst (Mihos & Hernquist 1994). As the new gas can come with different angular momentum, it is not necessary that orbits of fresh gas are aligned with that of the old stellar disk (Eliche-Moral et al 2011, Haynes et al 2000. Therefore, we believe that the current phase of star-burst in Mrk 996 has resulted from a recent tidal encounter, most likely a minor merger with a low-mass companion.…”
Section: Distribution Of Ionized Gas : Evidence Of Minor Mergermentioning
confidence: 99%